2017
DOI: 10.1016/j.clinbiomech.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of in-vivo articular cartilage contact surface of the knee during a step-up motion

Abstract: Background Numerous studies have reported on the tibiofemoral articular cartilage contact kinematics, however, no data has been reported on the articular cartilage geometry at the contact area. This study investigated the in-vivo tibiofemoral articular cartilage contact biomechanics during a dynamic step-up motion. Methods Ten healthy subjects were imaged using a validated magnetic resonance and dual fluoroscopic imaging technique during a step-up motion. Three-dimensional bone and cartilage models were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Another limitation is the absence of mechanical loading data. Although the locations of thickest CTh and densest sBMD agree with prior works reporting the areas of the femur in contact with the tibia during daily activities [ 16 , 29 , 34 , 35 ] and although the location of thickest CTh has been related to the knee flexion angle during walking [ 24 , 30 ], future studies should consider knee dynamics and loading patterns in addition to bone and cartilage properties for a global understanding of the osteochondral unit. In addition, the methodology is only applicable to non-OA knees, as measuring the location of thickest CTh is irrelevant in knees with substantial cartilage loss.…”
Section: Discussionsupporting
confidence: 83%
“…Another limitation is the absence of mechanical loading data. Although the locations of thickest CTh and densest sBMD agree with prior works reporting the areas of the femur in contact with the tibia during daily activities [ 16 , 29 , 34 , 35 ] and although the location of thickest CTh has been related to the knee flexion angle during walking [ 24 , 30 ], future studies should consider knee dynamics and loading patterns in addition to bone and cartilage properties for a global understanding of the osteochondral unit. In addition, the methodology is only applicable to non-OA knees, as measuring the location of thickest CTh is irrelevant in knees with substantial cartilage loss.…”
Section: Discussionsupporting
confidence: 83%
“…First, by using MRI-based 3D surface models, it is possible to re ect the thickness of the femoral and tibial cartilages in the results [40]. A cartilage-to-cartilage CP analysis during walking, lunging, and stair climbing has been reported using MRI-based 3D surface models [41][42][43]. Moro-oka et al…”
Section: Macwilliams Et Al Reported That Hamstring Co-contraction Decreases Tibial Internal Rotation During Kneementioning
confidence: 99%
“…Based on these studies, the authors suggest that medial femoral condyle cartilage is "adapted" to localized loading during gait 25 . Also in healthy individuals, Yin et al 26 analyzed in vivo tibiofemoral articular cartilage contact biomechanics during a dynamic step-up motion, using MRI and dual fluoroscopic imaging, and found that both the medial and lateral compartments of the knee experienced convex (femur) to convex (tibia) contact in the sagittal plane upon fitting a circle to the curvature of the femoral condyles and tibial plateaus. Together, these studies provide important baseline information regarding cartilage composition and morphology during various activities, which can serve as a point of comparison for identifying the development and progression of disease.…”
Section: Healthy and Oa Cartilage And Biomechanicsmentioning
confidence: 99%